Soft skills in chemistry courses: where, when, and how to assess them? - Sá, Jacinto; Sá, Jacinto (IJRDO- Journal of Educational Research, 2017)
A recent evaluation of chemistry degrees at Uppsala University, Sweden indicated that soft skills are not routinely assessed even if the report advocates that they are taught as an integrant part of the courses syllabus. This opinion article looks into case examples, strategies, and methodologies to assess soft skills as an integrant part of course assessment. Purposively, assessment strategies in courses dedicated to soft skills teaching and training were avoided.